Evaluasi Sensori Snack Bar Talipuk Dengan Penambahan Tepung Pisang Kepok (Musa paradisiaca forma typica) pada Panelis Anak-anak dan Dewasa: Sensory Evaluation of Talipuk Snack Bar (Nymphaea pubescens Willd) With the Addition of Kepok Banana Flour (Musa paradisiaca forma typica) on Children - Titis Linangsari; Dwi Sandri; Ema Lestari; Noorhidayah (Universitas Djuanda, 2022)
Talipuk seeds are one of the local food ingredients in South Kalimantan, which have the potential to be processed into various kinds of food, one of which is a snack bar. To increase the nutritional value of the talipuk snack bar, it is necessary to add kepok banana flour. The snack bar is a type of processed food with solid characteristics and is made from a combination of several food ingredients combined into one with the help of a binder. This study aimed to determine the best formulation of the talipuk snack bar with the addition of banana flour based on sensory tests from 30 panelists of children and 30 panelists of adults. The treatment in this study was the manufacture of talipuk snack bars with the addition of banana flour 0% (control), 25%, 50%, 75%, and 100%, the analysis used was a sensory test (taste, color, aroma, and texture) with preference (hedonic) and identified the best formulation with the De Garmo effectiveness index test. Sensory test results based on the De Garmo effectiveness index test showed that the best formulation in the children's hedonic test was found in the 100% banana flour formulation (de Garmo effectiveness value 0.87) with the values of each attribute: taste (1,95), color (1,93), aroma (1,93), texture (1,95). In the hedonic test with adult panelists, the best formulation results at 50% banana flour concentration (de Garmo effectiveness value 0,72) with each attribute: taste (5,99), color (6,38), aroma (6,02), and texture (6,35).